Archaic formulas of language etiquette as a representation of the specifics of the language picture of the world of Ukrainians - Hnatiuk, Lidiia (Ukrainian linguistics, 2022)
The article on the material of historical and dialect dictionaries, paroemias from the collections “Ukrainian proverbs, sayings, and the like” (collected by M. Nomys) and “Galician-Ukrainian folk tales” (collected, arranged and explained by Ivan Franko), as well as philosophical dialogues of H. Skovoroda, which represent the communication of educated Ukrainians of the 18th century, and interludes of the 17th–18th centuries, texts by I. Nekrashevych and “Aeneid” by I. Kotlyarevskyi, which show the folk formulas of language etiquette, considers the specifics of communicative behavior and language etiquette of Ukrainians of the past, including archaic etiquette formulas of greeting, farewell, apology, gratitude in different life situations that represented the specifics of the language picture of the world of our ancestors, in projection onto common forms of language etiquette, which are widely used today. Some of the formulas of language etiquette (including greeting, farewell, gratitude and apology), spread over the past centuries, are now almost completely obsolete (бодай здоров, будьте вибáчні до мене, Велик спасибог, добридóсвіток, магáй-бі, помагай-бі, помагай-бу; спаси Біг, спасибі благодарствую) or perceived by modern speakers as etiquette expressions with an archaic connotation (здрастуйте, ходи здоров, ходіть здорові, ідіть здорові, здорові ночуйте, простіть мені). Salutatory mini-dialogues, which clearly regulated what the one who greets first says, and what the interlocutor answers (Помагайбі! – Бодай здоров!; Бувайте здорові! – Ідіть здорові / Ходіть Здорові!) have become obsolete too. As a phenomenon of the communicative practice of Ukrainians in different areas remained the distinction добридень and день добрий (to those who were more respected) in Zhytomyr region, добрúдень (greetings in the morning) and день дóбрий (during the day and in the evening) in Kyiv region, etc. Although today’s Ukrainians may perceive certain elements of language etiquette of previous centuries as Russian (благодарствую), in fact, such components were common in Ukrainian language of the 16th – first half of the 17th century (long before Ukraine’s accession to Russia), and were an organic component of the language picture of the world of Ukrainians in the past. Information about the author: Lidiia Hnatiuk – Dr Hab, Prof. of the Department of the Ukrainian Language and Applied Linguistics; Educational and Scientific Institute of Philology; Taras Shevchenko National University of Kyiv (Ukraine). E-mail: lidahnatjuk@gmail.com __________ REFERENCES • Bohdan,S. K. (1998). Movnyi etyket ukraintsiv: tradytsii i suchasnist. Kyiv : Ridna mova (in Ukrainian). • Bohdan,S. K. (2003 a). Movnoetyketni odynytsi yak element indyvidualnoho styliu Volodymyra Svidzynskoho. Tvorchist Volodymyra Svidzynskoho. Lutsk, pp. 159–167 (in Ukrainian). • Bohdan,S. K. (2003 b). Stereotypy movnoi povedinky Shevchenka v yoho epistoliarii: zvertalni i proshchalni formuly, Shevchenkoznavchi studii, 5, 210–216 (in Ukrainian). • Bohdan,S. K. (2003 v). Formuly etyketu v ukrainskii epistoliarii. Urok ukrainskoi, 1, 30–34 (in Ukrainian). • Zhuravlova,N. M. (2002). Movnyi etyket ukrainskoi epistoliarii. Zaporizhzhia : ZDU (in Ukrainian). • Myroniuk,O. M. (1993). Istoriia ukrainskoho movnoho etyketu: (zasoby vyrazhennia vvichlyvosti). Extended abstract of Candidate’s thesis (Linguistics). Kyiv (іn Ukrainian). • Myroniuk, O. M. (2006). Istoriia ukrainskoho movnoho etyketu. Zvertannia. Kyiv : Lohos (іn Ukrainian). • Poslavska, N., Koliada, A. (2019). Formulae of speech etiquette in the texts of ukrainian folk tales. Problemy humanitarnykh nauk: zbirnyk naukovykh prats Drohobytskoho derzhavnoho pedahohichnoho universytetu imeni Ivana Franka. Seriia “Filolohiia”, 44, 69–82. https://doi.org/10.24919/2522-4557.2019.44.187338 (inUkrainian).